Handover initiation algorithm in hierarchical macrocell/femtocell In LTE network / Abdul Azim Mad Diah - Mad Diah, Abdul Azim (2013)
The fourth generation (4G) wireless technology known as Long Term Evolution (LTE) allows cellular operators to use new and wider spectrum and complements third generation (3G) networks with higher user data rates, lower latency and flat Internet Protocol (IP)-based network architecture. In L TE networks, the deployment of hierarchical macro/femto-cell networks is a great approach in improving the handoff procedures for a mobile station moving from a macrocell to a femtocell. Therefore, in this paper the initiation algorithm are proposed when a user enters the coverage area of the femtocell or macrocell. This handover initiation algorithm are based on the values of distance, speed and time when a MS moves from a serving Base Station (BS) to the target BS. The results shows that the proposed scheme using the proposed algorithm is effective in handover management towards minimizing the handover failures and unnecessary handovers.